A Strategic Role for Aircraft Manufacturers in Indonesia’s Sustainable Aviation - Ikhsani, Anugrah Fajar Iqbal; Putro, Utomo Sarjono (Integrasi Sains Media, 2025)
As Indonesia’s aviation industry enters a rapid phase of growth, questions around sustainability become increasingly urgent. While global targets such as IATA’s commitment to net-zero emissions by 2050 set a clear direction, applying these ambitions to an emerging market like Indonesia comes with its own set of challenges. This study explores how A Global Aircraft Manufacturer, one of the world’s leading aircraft manufacturers, can strategically contribute to Indonesia’s sustainable aviation goals. Using a qualitative approach supported by tools such as PESTLE, SWOT, TOWS, and Multi-Criteria Decision Analysis (MCDA), the research draws insights from interviews with A Global Aircraft Manufacturer leadership and local aviation experts. The findings highlight key strengths such as A Global Aircraft Manufacturer’s advanced fleet technology, operational know-how, and established partnerships as well as external barriers, including regulatory uncertainty, limited sustainable aviation fuel (SAF) infrastructure, and financial constraints among local carriers. From this analysis, four strategy pathways emerge: leading SAF policy development, supporting fleet modernization, promoting airline operational improvements, and facilitating ecosystem-wide SAF demonstration projects. Among these, the strategy focused on improving operational efficiency stands out as the most practical and impactful in the near term, offering a balance of feasibility, regulatory support, and measurable environmental benefit. This paper offers a grounded decision-making framework for global aerospace companies operating in emerging markets and provides practical direction for stakeholders aiming to accelerate Indonesia’s transition to more sustainable air travel.